RELASI FACEBOOK DENGAN BUDAYA POP DALAM PERSPEKTIF CULTURAL STUDIES (Telaah tentang Fenomena Facebooker di Kalangan Mahasiswa) - Prima Ayu Rizqi Maharani (Dialogia, 2015)
Abstract: The development of a global society in line with advances in information and communication technology leads the formation of the global village integrated through modern media communications. One way is to use social media among its interactive characteristics. From the results of the previous study authors found that social media most used by students STAIN Kediri is Facebook. This friendship site hegemony of students STAIN Kediri add a long line of development of popular culture facts as a result of development of communication technology that has changed the way students communicate. This suggests a cultural phenomenon in which new media shape popular culture that is associated with the daily problems that can be enjoyed by everyone or among certain people. By using the methods that are categorized as cultural studies theory of cultural studies revealed the fact that Facebook shaping behavior and its character is built on the fun but not substantial and alleviate people from work burnout throughout the day. Keywords: Facebook, Pop Culture dan Cultural Studies